Implementasi Aplikasi Rapor UTS Online Kurikulum Merdeka Di MTS Tarbiyatul Wathon Gresik - Lisdiyanto, Angga; ., Winarti; Andhyka, Awang; Mu'min, Syahri; Saputro, Arief; Nugroho, Rizky Aditya; Mufliq, Achmad; Abdillah, Ikhwan; Djanah, Miftahul; Lutfiyah, Nanik; Siswanto, Markhaban (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
After the Covid-19 pandemic, Indonesia's education system transformed with the introduction of the "Kurikulum Merdeka." However, its implementation remains limited. To support this, Universitas Nahdlatul Ulama Sidoarjo conducted a community service program (PKM) by developing an online report card web application at MTs Tarbiyatul Wathon Gresik. The target audience is school leaders and teachers. The methods used include lectures, discussions, and tutorials. The results show that the web application successfully facilitated the entry and monitoring of student grades, allowing data import from Excel to the application, and enabling easy printing of mid-term report cards. This application improves efficiency, organization, and flexibility in managing student grades, contributing positively to the educational transformation in the digital era.